PENGUATAN KADER TUBERKULOSIS PUSKESMAS GULUK-GULUK KEBUPATEN SUMENEP - Anggraini Sensusiati; Alfian Rosyid; Arina Puspitasari (Universitas Negeri Surabaya, 2022)
The purpose of this community service program is to empower the community, especially Tuberculosis (TB) cadres. With this program, hopefully the cadres will able to assist TB patients and identify TB suspect so that they want to check themselves at the Puskesmas and undergo treatment until they are healed. The long treatment time, the reluctance of TB patients to check themselves, coupled with the fear of being diagnosed with COVID-19 are some of the reasons why many TB patients and suspects in Sumenep Regency are not handled properly. One of the efforts that can be done to deal with the problem of TB is to provide companions for TB sufferers, which in this case is to empower TB cadres. In addition to providing assistance to TB sufferers whose condition has been confirmed, the cadres also play an important role in identifying people suspected of having TB. After successfully identifying suspected TB, the cadres need to encourage them to get checked and undergo treatment. Through this community service activity, cadres are given material and trained through simulations so that they can provide good assistance. The provision of materials is expected to provide refreshment and increase the knowledge of cadres about TB. Simulations are carried out so that cadres can improve their ability to provide assistance. In addition, it is hoped that this activity can support government programs in efforts to eradicate TB disease in Indonesia.